PECULIARITIES OF STYLISTIC DEVICES IN ENGLISH POETRY - Shamsiyeva Gulyora Orifovna (Bright Mind Publishing, 2025)
This article explores the unique characteristics and functions of stylistic devices in English poetry. Through the analysis of figurative language, sound devices, and structural techniques, it aims to reveal how poets employ stylistic means to enhance the emotional, aesthetic, and interpretive depth of their works. The study draws upon both classical and modern English poetry to exemplify how these devices shape meaning and reader perception.
Keywords: Stylistic devices, English poetry, figurative language, poetic structure, sound devices.